Мотивация в изучении иностранного языка у студентов младших курсов неязыковых специальностей - Терещенко, О.Б. (Культура народов Причерноморья, 2013)
В статье говорится о важной роли мотивации в изучении иностранных языков
студентами младших курсов неязыковых специальностей, рассматриваются главные виды мотивации и
стимулов к обучению иностранных языков, а также связанные с ними методические подходы и приемы.
Доказывается необходимость учитывать мотивацию студентов, обусловленную прежде всего
профессиональным познавательным интересом. На практических примерах показано, как на основе
коммуникативно-ориентированного обучения иностранному языку как подъязыку специальности
осуществляется взаимосвязанное аспектное обучение аудированию, говорению, чтению и письму. В
этой связи обосновывается большая эффективность выработки продуктивных умений у учащихся в
отличие от рецептивных умений и навыков на фоне систематических оценок и поощрения успехов
обучаемых.
Ключевые слова: мотивация, стимул, виды мотивации, изучение иностранного языка, методика
преподавания иностранных языков, студенты неязыковых специальностей. У статті йдеться мова про важливу роль мотивації у вивченні іноземних мов студентами
молодших курсів немовних спеціальностей, розглядаються головні види мотивації і стимулів до навчання
іноземних мов, а також пов'язані з ними методичні підходи і прийоми. Доводиться необхідність
враховувати мотивацію студентів, обумовлену передусім професійним пізнавальним інтересом. На
практичних прикладах показано, як на основі комунікативно-орієнтованого навчання іноземній мові як
под’язику спеціальності здійснюється взаємозв'язане аспектне навчання аудированию, мовленню,
читанню і письму. В зв'язку з цим обґрунтовується велика ефективність вироблення продуктивних умінь
у учнів на відміну від рецептивних умінь і навичок на тлі систематичних оцінок і заохочення успіхів
навчаних.
Ключові слова: мотивація, стимул, види мотивації, вивчення іноземної мови, методика викладання
іноземних мов, студенти немовних спеціальностей. The article highlights the problems of junior university students’ motivation to studying foreign
languages, which takes the topicality thanks to Bologna process. The author offers to understand the motivation
as a process, combining individual and situational parameters aiming to transformation of the subject situation
into the relevant motive. The author proves that the leading motive of the students should be awareness of the
necessity of foreign languages command for the successful professiaonal activity. But originally students are
influenced by the teacher’s motivation.
In this framework the levels of the formation of the teachers activity is presented together with the algorithm of
the practical study of the motives. On the basis of the literature survey common classification of the motives is
considered, as well as techniques, stimulating the process of communication. The examples are taken from the
soviet, foreign and modern Ukrainian literature on the methodology of teaching. These practical examples prove
that communication oriented teaching realizes interconnected teaching of listening, speaking, reading and
writing skills.
It’s argued that while teaching foreign language for special purposes the emphasis should be transferred from
the formation of receptive skills (reading and translation) into the working out of productive skills (speaking,
listening and writing). The article contains strategies and examples illustrating theabove statements.
In the conclusion the reasons, determing students’ motivation, are considered. It is proved that the most effective
way of foreign language teaching is an interactive work of a teacher and a student on the background of the
systematical estimation, encouragement and consideration of the professional interests of the students.
Key words: motivation, stimulus, types of motivation, studying of foreign languages, methods of teaching foreign
languages, students of nonlinguistic specialties.